Valor nutricional da massa de forragem de leguminosas e gramíneas em consorciação - Silva, Michele Simili da (2012)
The objective of this study was to evaluate the potential of mixtures, simple and com-plex, between legumes and grasses by production measurements of herbage mass, nutri-tional composition and balance between readily-available energy and protein. Two ex-periments were carried out at two locations Lévis and Normandin. The objective of the first experiment was todetermine the best combination of a single grass species and one of the legume species. Six grass species, timothy (Phleum pratense L.), Kentucky blue-grass (Poa pratensis L.), tall fescue (Festuca arundinacea Schreb.), orchardgrass (Dac-tylis glomerata L.), meadow bromegrass (Bromus biebersteinii Roemer&J.A. Schultes), and meadow fescue (Festuca elatior L.) were seeded with one of three leg-ume species, alfalfa (Medicago sativa L.), white clover (Trifolium repens L.), and birds-foot trefoil (Lotus corniculatus L.) at two sites. Carbohydrate and protein fractions us-ing the Cornell net carbohydrate and protein system along with other nutritive value at-tributes and dry matter (DM) yield were determined at the two first harvests of the first production year. Grass and legume species in the mixture significantly affected most attributes. Alfalfa mixtures had greater ratios of water soluble carbohydrates (WSC) to crude protein (CP) and carbohydrate fractions A+B1 to protein fractions A+B1 also had greater acid detergent fiber (ADF) and neutral detergent fiber (aNDF) concentrations, and lower in vitro neutral detergent fiber digestibility (dNDF), and in vitro true DM di-gestibility (IVTD) than the average of the three legume species with similar DM yield. Mixtures with meadow fescue and tall fescue had greater WSC/CP ratio, DM yield, and ADF and NDF concentrations than the average of the six grass species. Mixtures of meadow fescue with any of the three legume species generally had the best combination of high ratios of WSC/CP and DM yield. The alfalfa and meadow fescue mixture had numerically the best WSC/CP ratio (0.70), the highest DM yield but low average IVTD. The objective of the second experiment was compare four grass mixtures combined with two forage legumes ( grazing type alfalfa, A, Medicago sativa L. cv. CRS1001) or birdsfoot trefoil, B, Lotus corniculatus L. cv. AC Langille). The grass mixtures used were: 1)timothy, meadow fescue, reed canarygrass and Kentucky bleugrass; 2)Kentucky bluegrass, tall fescue, orchardgrass and meadow brome; 3) meadow fescue, timothy and Kentucky bluegrass; 4) reed canarygrass, Kentucky bluegrass, tall fescue and Meadow brome. The eight forage mixtures were seeded at two sites with legume species as main plots and grass species mix as subplots. Data were averaged across the two sites and the two first harvests of the first production year and analysed by ANOVA followed by a principal component analysis. Alfalfa-based mixtures had greater ADF, NDF, and TC concentrations, greater WSC/CP and (CA+CB1)/(PA+PB1) ratios, and lower concentra-tions of TN and PA than the average of the eight complex mixtures. The grass species mixes with meadow fescue had the greater DM yield compared to the average of the eight complex mixtures. The MfTiKb grass species mix had a lower ADF concentration and greater dNDF and IVTD, whereas the TiMfRcKb grass species mix had greater WSC/CP and CB1+CA/PB1+PA ratios than the average of the eight complex mixtures. The ATiMfRcKb complex mixture had the greatest WSC/CP ratio. The complex mix-tures with alfalfa and meadow fescue had the best energy/protein ratio and DM yield. Mixtures of meadow fescue with alfalfa, white clover, or birdsfoot trefoil generally pro-vided the best combination of a high energy/protein ratio, high DM yield, and good di-gestibility. The mixture of alfalfa with meadow fescue had the best energy/protein bal-ance and DM yield but a low average digestibility. The TiMfRcKb grass species mix provided the combination of high readily-available energy to protein balance and high DM yield. The complex mixtures with alfalfa and meadow fescue had the best readily- available energy to protein ratio and DM yield. These results from the first two harvests of the first production year provide useful and novel information on the desired species composition of binary mixtures that combine energy to protein ratio and DM.